Sahir Ludhianvi : the people's poet - Manwani, Akshay (Noida HarperCollins, 2013)
Sahir Ludhianvi is probably the only songwriter in Hindi films whosepoetry was accepted in its purest form and incorporated as a filmsong. So great was his stature as an Urdu poet that he never hadto mould his poetry to suit the demands of film songwriting; instead, producers and composers adapted their requirements to his poetry. Hissongs in films like Pyaasa, Naya Daur and Phir Subah Hogi have attainedthe status of classics. This exhaustive biography traces the poets rich life, from his troubledchildhood and his equally troubled love relationships, to his rise as oneof the pre-eminent personalities of the Progressive Writers Movementand his journey as lyricist through the golden era of Hindi film music, the1950s and 1960s.
Keywords: Poets, Urdu; Biography; Film